2020
DOI: 10.3390/cells9092062
|View full text |Cite
|
Sign up to set email alerts
|

Formation of βTC3 and MIN6 Pseudoislets Changes the Expression Pattern of Gpr40, Gpr55, and Gpr119 Receptors and Improves Lysophosphatidylcholines-Potentiated Glucose-Stimulated Insulin Secretion

Abstract: The impaired spatial arrangement and connections between cells creating islets of Langerhans as well as altered expression of G protein-coupled receptors (GPCRs) often lead to dysfunction of insulin-secreting pancreatic β cells and can significantly contribute to the development of diabetes. Differences in glucose-stimulated insulin secretion (GSIS) are noticeable not only in diabetic individuals but also in model pancreatic β cells, e.g., βTC3 and MIN6 β cell lines with impaired and normal insulin secretion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…Since similar ligands (LCFAs) also target GPR120 [ 7 ], we included the latter in the analysis. Previously, we confirmed GPR40, GPR55, and GPR119 expression in a MIN6 cell line [ 12 ], and the expression of GPR120 was also identified in this cell line [ 20 ].…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Since similar ligands (LCFAs) also target GPR120 [ 7 ], we included the latter in the analysis. Previously, we confirmed GPR40, GPR55, and GPR119 expression in a MIN6 cell line [ 12 ], and the expression of GPR120 was also identified in this cell line [ 20 ].…”
Section: Resultssupporting
confidence: 67%
“…Our previous studies indicated that in MIN6 cells LPCs with lauroyl (12:0), mirystoyl (14:0), palmitoyl (16:0), stearolyl (18:0), and oleoyl (18:1) fatty acid residues significantly potentiated the level of GSIS above the control level (from 1.5 to 3.5-fold). In this case, LPCs bearing longer acyl chains tended to stimulate MIN6 cells stronger than those bearing medium acyl chains [ 12 ]. Additionally, we demonstrated that LPC bearing oleoyl and palmitoyl fatty acid residues augmented GSIS by targeting GPR40, GPR55, and GPR119 receptors, which represent a novel antidiabetic approach [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 We have previously demonstrated the expression of Gpr40 , Gpr55 , and Gpr119 in MIN6 cells. 47 Here, we have detected all transcripts in both cell lines studied. In MIN6 cells Gpr40 mRNA was the most abundant, followed by Gpr120 .…”
Section: Resultsmentioning
confidence: 61%
“…The increase in BBB permeability produced by FFA1 receptor activation is significant given the fact that the endogenous agonist of the receptor, DHA is present in the diet, dietary supplements, and component of lipid-lowering drugs [3,4]. Lysophosphatidylcholine (LPC), an endogenous ligand for GPR119 receptor, has also been reported to exert some of its metabolic effects by activating FFA1/GPR40 and GPR55 [54][55][56]. Moreover, FFA1-selective agonists are still being considered as potential therapeutic agents for the treatment of metabolic disorders such as type 2 diabetes [57][58][59].…”
Section: Discussionmentioning
confidence: 99%